TO ISSUE OF EFFICIENCY VEHICLE SERVICE MULTIPLE ROUTES BY THE SAME TYPE VEHICLES - , А. С., К. В., А. О., М. О. (Municipal economy of cities. Series: «Economy science», 2017)
The article aims at improving the efficiency of transport services on several routes terms of redistribution between vehicles in a variety of rush hour service for all traffic volumes. The mechanism and model estimate the number of vehicles compatible with their service routes on freight and passenger transport. The mutual and joint vehicles’ operation on different routes using proposed redistribution mechanism, reduce the total stocks on 7.5% than traditional services. Reducing the number of vehicles reduces capital expenditures and payments on borrowed capital, which positively reflected on the net present value compared to the existing version. Obtained results may be used in planning and organizing routes in the city and land values combined with a short arm (120 km) and regular transportation. Keywords: route, vehicle, ridership, irregularity, project turnaround time